Influence of cardiorespiratory fitness and parental lifestyle on adolescents' abdominal obesity - Vale, Susana (2016)
The aims of this study were (1) to analyse the influence of cardiorespiratory fitness (CRF) and parental overweight status (POS) and socioeconomic status (SES) on abdominal obesity. This study was comprised of 779 adolescents (12-18 years). Waist-height ratio (WHtR), 20 m shuttle-run test to ascertain CRF, POS according to World Health Organization recommendations and SES of parents using level of education were analysed. Using WHtR, the prevalence of abdominal obesity was 21.3% (23.5% girls and 17.9% boys; p = 0.062). Regardless of gender, participants who belonged to the WHtR risk group had significantly (p ≤ 0.05) lower CRF scores than the WHtR non-risk group; 84.4% of girls who belonged to the WHtR risk group had one or two overweight parents (p ≤ 0.05). Boys with low CRF (OR: 6.43; CI: 3.33-12.39) were more likely to belong to the WHtR risk group compared with their lean peers. Girls with low CRF (OR: 1.78; CI: 1.14-2.78) and with at least one overweight parent (OR: 2.50; CI: 1.07-5.85) or two overweight parents (OR: 4.90; CI: 2.08-11.54) were associated with the risk of abdominal obesity. This study highlights the influence of adolescents' family on abdominal obesity, especially in girls. Further, the data suggested that low CRF was a strong predictor of risk values of abdominal obesity in adolescence.